Vertically-oriented ceramic fiber / polymer composite solid electrolyte membrane and preparation method and application thereof

By using a vertically oriented inorganic ceramic nanofiber/polymer composite solid electrolyte membrane in lithium metal batteries, the problem of excessive tortuosity of ion transport of ceramic fiber-based composite solid electrolyte is solved, and higher ion conductivity and battery performance are achieved.

CN119518082APending Publication Date: 2025-02-25DONGHUA UNIV
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411670099.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The ion transport of ceramic fiber-based composite solid electrolyte is too high, resulting in unsatisfactory ion conductivity, limiting the safety performance, rate performance and cycle life of lithium metal batteries.

Method used

A vertically oriented inorganic ceramic nanofiber/polymer composite solid electrolyte membrane is used to prepare an inorganic ceramic nanofiber network with continuous and fast lithium ion transmission capabilities by electrospinning and calcining processes, and the polymer/lithium salt composite is poured thereon.

Benefits of technology

The ionic conductivity of the composite solid electrolyte is significantly improved, and the safety performance, rate performance and cycle life of lithium metal batteries are enhanced. At the same time, the preparation method is low in cost and high efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119518082A_ABST
    Figure CN119518082A_ABST
Patent Text Reader

Abstract

The invention relates to a vertical orientation ceramic fiber / polymer composite solid electrolyte membrane and a preparation method and application thereof, the vertical orientation ceramic fiber / polymer composite solid electrolyte membrane is composed of an inorganic framework material with a vertical orientation structure and a toughening matrix material filled in the inorganic framework material, the inorganic framework material is an inorganic ceramic nanofiber with high lithium ion conductivity, the toughening matrix material is a polymer / lithium salt compound with relatively high lithium ion conductivity. The composite solid electrolyte membrane combines high modulus of an inorganic skeleton and high toughness of a polymer, has excellent mechanical properties, and can form good contact with a positive electrode and a negative electrode of a battery. More importantly, the unique vertical orientation fiber structure of the inorganic skeleton can greatly reduce the actual transmission path of ions in the operation process of the battery, and the ionic conductivity of the composite solid electrolyte membrane is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid-state lithium metal batteries, and in particular to a vertically oriented ceramic fiber / polymer composite solid electrolyte membrane and a preparation method and application thereof. Background Art

[0002] Lithium metal batteries are widely considered to be the best choice for next-generation efficient energy storage due to their ultra-high theoretical energy density. However, the large-scale commercial application of lithium metal batteries has been limited by the unsatisfactory performance of solid-state electrolytes. As an alternative to liquid electrolytes, non-flammable and non-volatile solid electrolytes are essential to ensure the safe and stable operation of lithium metal batteries. However, low ionic conductivity and poor contact with the electrode interface remain two major challenges hindering the development of solid-state electrolytes.

[0003] Among various types of solid electrolytes, composite solid electrolytes composed of polymer / lithium salt matrix and inorganic ceramic filler combine the advantages of close interfacial contact between solid polymer electrolyte and electrode and excellent ion transport capacity of inorganic electrolyte. Therefore, extensive research has focused on the construction of reliable composite solid electrolytes. By introducing active ceramic particles into the polymer matrix, the crystallization of the polymer can be suppressed, resulting in more amorphous regions, thereby improving the overall ionic conductivity of the composite solid electrolyte. In addition, the change of local polymer chain conformation caused by the surface groups of ceramic particles and the increase of free Li + The concentration of the polymer and ceramic particles forms a fast ion transport path between them. As the content of ceramic particles increases, an interconnected percolation network gradually forms between the particles, which further enhances the ionic conductivity of the composite solid electrolyte. However, excessive addition causes agglomeration between the ceramic particles, thereby destroying the percolation network and causing a decrease in ionic conductivity.

[0004] Considering the continuity of fiber materials in three-dimensional space, in recent years, pre-constructing a ceramic nanofiber percolation network with fast ion transport capability and then further infusing a polymer / lithium salt matrix to prepare a ceramic fiber-based composite solid electrolyte is a promising approach. However, ceramic nanofibers tend to be randomly distributed in three-dimensional space, which greatly increases the actual ion transport path length in the composite solid electrolyte, thereby hindering the improvement of the ionic conductivity of the ceramic fiber-based composite solid electrolyte.

[0005] In response to the above problems, it is urgent to develop a ceramic fiber-based composite solid electrolyte with low ion transport tortuosity to further improve its ionic conductivity. Summary of the invention

[0006] In view of the shortcomings of the above-mentioned technology, the purpose of the present invention is to provide a new method for preparing a vertically oriented ceramic fiber / polymer composite solid electrolyte membrane, so as to solve the problem that the ion transmission tortuosity of the ceramic fiber-based composite solid electrolyte in the prior art is too high, resulting in unsatisfactory ion conductivity. The use of the composite solid electrolyte membrane improves the safety performance, rate performance and cycle life of lithium metal batteries.

[0007] One aspect of the present invention provides a vertically oriented ceramic fiber / polymer composite solid electrolyte membrane, which is composed of an inorganic skeleton material with a vertically oriented structure and a toughening matrix material filled in the inorganic skeleton material, wherein the inorganic skeleton material is an inorganic ceramic nanofiber with high lithium ion conductivity, and the toughening matrix material is a polymer / lithium salt composite with relatively high lithium ion conductivity.

[0008] Another aspect of the present invention provides a method for preparing a vertically oriented ceramic fiber / polymer composite solid electrolyte membrane, specifically:

[0009] The inorganic ceramic nanofibers and the spinning aid polyvinyl pyrrolidone are fully mixed and dissolved in an organic solvent to form a spinning solution, and an oriented inorganic ceramic nanofiber precursor film is obtained by electrostatic spinning and collected by a high-speed receiving roller. A vertically oriented inorganic ceramic nanofiber precursor array cylinder is then formed by winding, and then a vertically oriented inorganic ceramic nanofiber array cylinder is obtained by a calcination process. A solution containing a toughening matrix material is continuously poured into the cylinder to remove the organic solvent component therein, and finally the vertically oriented inorganic ceramic nanofiber / polymer composite solid electrolyte membrane is obtained by cutting with a thinning slicer.

[0010] A solid-state lithium metal battery comprises a positive electrode, a negative electrode and the vertically oriented ceramic fiber / polymer composite solid electrolyte membrane of the present invention.

[0011] Principle of the invention: The inorganic skeleton material in the composite solid electrolyte provided by the present invention is an inorganic ceramic nanofiber network with continuous and rapid lithium ion transmission capability, and the inorganic ceramic nanofiber presents a vertically oriented structural feature. Firstly, the rapid lithium ion transmission capability of the inorganic skeleton material comes from the ceramic material itself, that is, lithium ions can be rapidly transmitted through vacancies and gaps in the crystal structure of this series of ceramic materials, and can also migrate rapidly through grain boundaries; on the other hand, by introducing ceramic materials into the polymer matrix, the crystallization of the polymer can be inhibited, and more amorphous regions can be produced, thereby improving the overall ionic conductivity of the composite solid electrolyte. In addition, the changes in the local polymer chain conformation caused by the surface groups of the ceramic particles and the increase in free Li +concentration, and can also form a fast ion transmission path between the polymer and the ceramic material surface. It is worth noting that thanks to the continuity of the fiber material, the fast lithium ion transmission path brought by the inorganic skeleton material can be continuous and uninterrupted in three-dimensional space. More importantly, the vertically oriented inorganic ceramic nanofiber structure can minimize the actual path length of the lithium ion transmission process, so that the transmission of lithium ions between the positive and negative electrodes of the battery is not only fast and continuous, but also the shortest path. This unique structural design greatly improves the ionic conductivity of the composite solid electrolyte, and improves the safety performance, rate performance and cycle life of lithium metal batteries. In addition, the essence of the preparation method for constructing this unique vertically oriented structure is to use direct mechanical force as the driving force (including the orientation force of the high-speed receiving roller, the winding force and the shear force during the slicing process) to induce the vertical orientation of inorganic ceramic nanofibers, which has the significant advantages of high efficiency and low cost.

[0012] Compared with the prior art, the effects of the present invention are as follows:

[0013] (1) Vertically oriented inorganic ceramic nanofibers as inorganic skeleton materials not only provide fast and continuous ion transport channels, but also minimize the actual path length during lithium ion transport, further improving the ionic conductivity of the composite solid electrolyte and improving the safety performance, rate performance and cycle life of lithium metal batteries.

[0014] (2) The driving force used in the preparation method for constructing this vertically oriented inorganic ceramic nanofiber structure is mechanical force, which is low-cost and high-efficiency. It is expected to be promoted and applied on a large scale and has potential commercial value. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is an optical digital photograph of the vertically oriented ceramic fiber / polymer composite solid electrolyte membrane provided in Example 1 of the present invention.

[0016] Figure 2 This is a scanning electron microscope photograph of the cross section of the vertically oriented ceramic fiber / polymer composite solid electrolyte membrane provided in Example 1 of the present invention.

[0017] Figure 3 This is a scanning electron microscope photograph of the surface of the vertically oriented ceramic fiber / polymer composite solid electrolyte membrane provided in Example 1 of the present invention.

[0018] Figure 4 Scanning electron microscope photos of the cross section of the parallel oriented ceramic fiber / polymer composite solid electrolyte membrane provided in Comparative Example 1 of the present invention at different magnifications. The magnification of (a) is 100 μm; the magnification of (b) is 20 μm.

[0019] Figure 5 The performance comparison diagrams of Example 1 of the present invention and Comparative Example 1 are shown in FIG. (a) is a comparison diagram of the ionic conductivity of the composite solid electrolyte provided in Example 1 of the present invention and Comparative Example 1 at different temperatures; (b) is a comparison diagram of the Li-LFP full-cell rate performance of the composite solid electrolyte provided in Example 1 of the present invention and Comparative Example 1; (c) is a comparison diagram of the Li-LFP full-cell long-cycle performance of the composite solid electrolyte provided in Example 1 of the present invention and Comparative Example 1; (d) is a comparison diagram of the Li-Li symmetric battery long-cycle performance of the composite solid electrolyte provided in Example 1 of the present invention and Comparative Example 1.

[0020] Figure 6 This is a schematic diagram of the process flow of the method for preparing the vertically oriented ceramic fiber / polymer composite solid electrolyte membrane provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0021] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0022] A vertically oriented ceramic fiber / polymer composite solid electrolyte membrane, the composite solid electrolyte membrane is composed of an inorganic skeleton material with a vertically oriented structure and a toughening matrix material filled in the inorganic skeleton material, the inorganic skeleton material is an inorganic ceramic nanofiber with high lithium ion conductivity, and the toughening matrix material is a polymer / lithium salt composite with relatively high lithium ion conductivity.

[0023] Preferably, the inorganic skeleton material of the present invention is an inorganic ceramic nanofiber having a continuous fast ion transport path prepared by electrospinning and subsequent high-temperature calcination process.

[0024] Preferably, the inorganic ceramic nanofibers of the present invention are at least one or more of the perovskite-type ceramic lithium lanthanum titanate (LLTO), garnet-type ceramic lithium lanthanum zirconium oxide (LLZO), sodium superionic conductor-type ceramic lithium aluminum germanium phosphate (LAGP), lithium aluminum titanium phosphate (LATP) and all corresponding heteroelement-doped modified variant ceramics.

[0025] Preferably, in the inorganic skeleton material structure of the present invention, the inorganic ceramic nanofibers present a highly ordered orientation structure and are oriented at any angle to the plane of the entire composite solid electrolyte membrane.

[0026] Preferably, in the inorganic skeleton material structure of the present invention, the inorganic ceramic nanofibers present a highly ordered orientation structure and are arranged vertically at an angle of 90° to the plane of the entire composite solid electrolyte membrane.

[0027] Preferably, the polymer in the toughened matrix material of the present invention is at least one or more of polyethylene oxide (PEO), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), and polymethyl methacrylate (PMMA).

[0028] Preferably, the lithium salt in the toughened matrix material of the present invention is at least one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium bis(oxalatoborate) (LiBOB), and lithium difluorooxalatoborate (LiDFOB).

[0029] Preferably, the mass ratio of the inorganic skeleton material to the toughening matrix material of the present invention is 10-60%:40-90%, and the sum of the mass ratios of the two is 100%; and the mass ratio of the polymer and the lithium salt in the toughening matrix material is 80-90%:10-20%, and the sum of the mass ratios of the two is 100%.

[0030] Preferably, the composite solid electrolyte membrane of the present invention has a thickness of 50 to 300 μm.

[0031] A method for preparing a vertically oriented ceramic fiber / polymer composite solid electrolyte membrane, specifically:

[0032] The inorganic ceramic nanofibers and the spinning aid polyvinyl pyrrolidone (PVP) are fully mixed and dissolved in an organic solvent to form a spinning solution, and an oriented inorganic ceramic nanofiber precursor film is obtained by electrostatic spinning and collected by a high-speed receiving roller. A vertically oriented inorganic ceramic nanofiber precursor array cylinder is then formed by winding, and then a vertically oriented inorganic ceramic nanofiber array cylinder is obtained by a calcination process. A solution containing a toughening matrix material is continuously poured into the cylinder to remove the organic solvent component therein, and finally the vertically oriented inorganic ceramic nanofiber / polymer composite solid electrolyte membrane is obtained by cutting with a thinning slicer.

[0033] Preferably, the organic solvent in the spinning solution of the present invention is N,N-dimethylformamide, the weight average molecular weight of the spinning aid polyvinyl pyrrolidone is 1300000 g / mol, the concentration is 6-14 wt%, and the concentration of various salts containing metal elements required for inorganic ceramic nanofibers is 15-25 wt%;

[0034] Preferably, the electrospinning conditions of the present invention include:

[0035] The positive voltage is 10~20kV, the negative voltage is -2~0kV,

[0036] The spinning temperature is 20-40°C, the spinning humidity is controlled at 20-50% RH, and the spinning time is 2-8 hours.

[0037] The spinning needle injection speed is 0.4-1mL / h, and the receiving distance is 10-20cm.

[0038] The high-speed receiving roller has a diameter of 5 to 15 cm and a rotation speed of 2000 to 4000 rpm.

[0039] Preferably, in the calcination process of the present invention, a staged heating method is adopted to achieve the removal of the spinning aid polyvinyl pyrrolidone and the formation of the inorganic ceramic nanofibers; the heating program is:

[0040] The temperature was raised from room temperature to 100°C for 40 minutes.

[0041] The temperature rises from 100°C to 600°C, and the heating time is 370 minutes.

[0042] The temperature rises from 600℃ to 800℃, and the heating time is 70min.

[0043] The mixture was kept at 800°C for 600 min and then naturally cooled to room temperature.

[0044] Preferably, in the solution containing the toughening matrix material of the present invention, the concentration of the toughening matrix material is 5-10 wt %, and the organic solvent selected is one or more of acetonitrile, DMF, chloroform and the like.

[0045] Preferably, the present invention performs thinning and slicing in a low temperature environment of -20 to 10°C, and the slicing is performed perpendicular to the orientation direction of the inorganic ceramic nanofibers. The slice thickness is set by a slicer and controlled within a range of 50 to 300 μm.

[0046] A solid-state lithium metal battery comprises a positive electrode, a negative electrode and the vertically oriented ceramic fiber / polymer composite solid electrolyte membrane of the present invention.

[0047] The present invention provides a vertically oriented ceramic fiber / polymer composite solid electrolyte membrane and a preparation method and application, which is composed of an inorganic skeleton material that performs fast ion conduction and a toughening matrix material filled in the skeleton material. The inorganic skeleton material is selected from inorganic ceramics with high lithium ion conductivity, which presents a fiber morphology with a vertically oriented structure, and the toughening matrix material is selected from polymer / lithium salt complexes with high lithium ion conductivity, which are uniformly filled in the entire inorganic skeleton material. The composite solid electrolyte membrane combines the high modulus of the inorganic skeleton and the high toughness of the polymer, and not only has excellent mechanical properties, but also can form good contact with the positive and negative electrodes of the battery. More importantly, the unique vertically oriented fiber structure of its inorganic skeleton can greatly reduce the actual transmission path of ions during battery operation, greatly improving the ionic conductivity of the composite solid electrolyte membrane. The use of the composite solid electrolyte membrane improves the safety performance, rate performance and cycle life of lithium metal batteries. In addition, a high-speed receiving roller is used to collect the electrospun fibers to prepare highly oriented nanofiber membranes. Combined with the subsequent winding, calcination, infusion of polymer / lithium salt complexes and thinning and slicing, this creatively achieves the vertically oriented and orderly arrangement of ceramic nanofibers in the composite solid electrolyte, providing a guarantee for the future large-scale preparation of this type of composite solid electrolyte with a specific structure.

[0048] The analysis method in the embodiment of the present invention is as follows:

[0049] The surface and cross-sectional micromorphology of the composite solid electrolyte membrane were analyzed using a scanning electron microscope (SEM) model JSM-7500F of JEOL Ltd. (JEOL);

[0050] The DH7000 electrochemical workstation of Jiangsu Donghua Analytical Instrument Co., Ltd. was used to test the ionic conductivity of the composite electrolyte membrane;

[0051] The battery testing system model MIHW-200-160CH-B of Shenzhen Xinwell Electronics Co., Ltd. was used to perform Li-LFP full battery rate and long cycle performance tests at constant temperature, as well as Li-Li symmetric battery long cycle performance tests.

[0052] Example 1

[0053] (1) Prepare LLTO electrospinning solution (chemical formula: Li 0.33 La 0.56TiO3). First, add 31g of DMF and 4g of acetic acid solution into the bottle, then add lithium nitrate (0.524g, 15wt% excess), lanthanum nitrate hexahydrate (4.85g), and tetrabutyl titanate (6.806g) into the bottle according to a fixed stoichiometric ratio, and stir the prepared solution for two hours. After the salt is completely dissolved, add the pre-prepared PVP powder (5g). Finally, stir the mixed solution overnight to complete the preparation of the electrospinning solution.

[0054] The prepared spinning solution is placed in a 10mL syringe in the electrospinning machine for spinning. Before spinning begins, the temperature needs to be set to room temperature 25°C and the humidity needs to be set to 50%. The positive high voltage of the spinning machine is set to 15kV, the negative high voltage is set to -1kV, and then the injection speed is set to 0.8mL / h. Next, adjust the speed of the high-speed receiving roller to 2800rpm to start the spinning process. The spinning time is 10h.

[0055] After spinning, the successfully prepared oriented fiber membrane was cut into strips with a width of 1 cm perpendicular to the fiber orientation direction, and then the cut strips were continued to be wound perpendicular to the fiber orientation direction to form a cylindrical block.

[0056] The cylindrical block is placed into an alumina ceramic mold that matches its size and shape, and the whole is placed into a tubular furnace for high-temperature sintering using a specific procedure to obtain the vertically oriented LLTO nanofiber array cylinder required by the present invention.

[0057] (2) The vertically oriented LLTO nanofiber array cylinder obtained in step (1) was moved into a customized polytetrafluoroethylene mold and placed in a glove box for later use.

[0058] (3) PEO (weight average molecular weight 600000 g / mol) was added to acetonitrile in a certain proportion, and after being fully dissolved, the solution was moved into a glove box to prepare the electrolyte.

[0059] (4) Add a certain amount of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) to the acetonitrile solution of PEO in the glove box and stir for two hours until the lithium salt dissolves. After the lithium salt dissolves, pour the solution into the vertically oriented LLTO nanofiber array cylinder, wait for the solution to fully infiltrate, and then transfer it to a blast oven set at 80°C in the glove box to quickly remove the solvent acetonitrile. When the liquid level is about to be lower than the vertically oriented LLTO nanofiber array cylinder, add the solution in time and repeat the above steps several times. Finally, transfer it to a vacuum oven and vacuum dry it at 100°C to continue to remove the residual acetonitrile to obtain a vertically oriented LLTO nanofiber array / toughened matrix material composite block.

[0060] (5) The composite block is thinned and sliced ​​perpendicular to the fiber orientation direction using a thinning slicer. The ambient temperature is controlled at 0°C during slicing, and the slice thickness is 200 μm. Finally, a vertically oriented LLTO nanofiber / PEO composite solid electrolyte membrane is obtained, which is denoted as VLLTO.

[0061] Depend on Figure 1 It can be seen that the prepared VLLTO appears white on a macroscopic scale and has an obvious concentric circle structure formed by the winding process.

[0062] Depend on Figure 2 It can be seen that the thickness of the prepared VLLTO is 200 μm, and the LLTO nanofibers are arranged vertically at the microscopic level, and the PEO / LiTFSI composite is uniformly filled therein.

[0063] Depend on Figure 3 It can be seen that the microscopic morphology of the prepared VLLTO on the surface also presents an obvious concentric circle structure, in which the bright part is the LLTO nanofibers and the dark part is the PEO / LiTFSI composite.

[0064] The general preparation method of this type of vertically oriented ceramic fiber / polymer composite solid electrolyte membrane can be as follows: Figure 6 The schematic diagram of the process is summarized.

[0065] Example 2

[0066] This embodiment provides a composite solid electrolyte and a preparation method thereof, which is different from the embodiment 1 in that the type of inorganic skeleton material is different. The spinning solution in (1) of the embodiment 1 is replaced with LLZAO electrospinning solution (specific chemical formula is Li 6.4 La3Zr2Al 0.2 O 12 ). First, add 23g of DMF and 2g of acetic acid solution into the bottle, then add lithium nitrate (0.531g, 15wt% excess), lanthanum nitrate hexahydrate (1.299g), zirconium n-propoxide (70wt% dispersed in 1-propanol, 0.936g), and aluminum nitrate nonahydrate (0.075g) into the bottle according to a fixed stoichiometric ratio, and stir the prepared solution for two hours. After the salt is completely dissolved, add the pre-prepared PVP powder (2.25g). Finally, stir the mixed solution overnight to complete the preparation of the electrospinning solution. The remaining steps are the same as in Example 1. The prepared composite solid electrolyte membrane is recorded as VLLTO-2.

[0067] Example 3

[0068] This embodiment provides a composite solid electrolyte and a preparation method thereof, which differs from the embodiment 1 in that the type of toughening material is different. The polymer in (3) of the embodiment 1 is replaced by PVDF-HFP (weight average molecular weight is 400000 g / mol), and the solvent required for dissolution is replaced by DMF. The remaining steps are the same as those of the embodiment 1. The prepared composite solid electrolyte membrane is recorded as VLLTO-3.

[0069] Example 4

[0070] This embodiment provides a composite solid electrolyte and a preparation method thereof, which differs from Embodiment 1 in that the type of lithium salt is different. LiTFSI in (4) of Embodiment 1 is replaced by lithium bis(fluorosulfonyl)imide (LiFSI), and the remaining steps are the same as those of Embodiment 1. The prepared composite solid electrolyte membrane is denoted as VLLTO-4.

[0071] Example 5

[0072] This embodiment provides a composite solid electrolyte and a preparation method thereof, which differs from Embodiment 1 in that the thickness of the electrolyte membrane is different. The slice thickness in (5) of Embodiment 1 is changed to 100 μm, and the remaining steps are the same as those of Embodiment 1. The prepared composite solid electrolyte membrane is denoted as VLLTO-5.

[0073] Comparative Example 1

[0074] (1) Prepare LLTO electrospinning solution (chemical formula: Li 0.33 La 0.56 TiO3). First, add 31g of DMF and 4g of acetic acid solution into the bottle, then add lithium nitrate (0.524g, 15wt% excess), lanthanum nitrate hexahydrate (4.85g), and tetrabutyl titanate (6.806g) into the bottle according to a fixed stoichiometric ratio, and stir the prepared solution for two hours. After the salt is completely dissolved, add the pre-prepared PVP powder (5g). Finally, stir the mixed solution overnight to complete the preparation of the electrospinning solution.

[0075] The prepared spinning solution is placed in a 10mL syringe in the electrospinning machine for spinning. Before spinning, the temperature needs to be set to room temperature 25°C and the humidity needs to be set to 50%. The positive high voltage of the spinning machine is set to 15kV, the negative high voltage is set to -1kV, and then the injection speed is set to 0.8mL / h. Then, adjust the speed of the high-speed receiving roller to 2800rpm to start the spinning process. The spinning time is 10h.

[0076] The fiber membrane obtained after spinning is placed in a tubular furnace and sintered at high temperature using a specific procedure to obtain the desired oriented LLTO nanofiber membrane.

[0077] (2) The oriented LLTO nanofiber membrane obtained in step (1) was transferred to a customized polytetrafluoroethylene mold and placed in a glove box for later use.

[0078] (3) PEO (weight average molecular weight 600000 g / mol) was added to acetonitrile in a certain proportion, and after being fully dissolved, the solution was moved into a glove box to prepare the electrolyte.

[0079] (4) Add a certain amount of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) to the acetonitrile solution of PEO in a glove box and stir for two hours until the lithium salt dissolves. After the lithium salt dissolves, pour the solution into the oriented LLTO nanofiber membrane, wait for the solution to be fully infiltrated, and then transfer it to a blast oven in the glove box set at 80°C to quickly remove the solvent acetonitrile. Finally, transfer it to a vacuum oven and vacuum dry it at 100°C to continue to remove the residual acetonitrile, control the thickness to 200μm, and keep the LLTO nanofiber content consistent with Example 1, and finally obtain a parallel oriented LLTO nanofiber / PEO composite solid electrolyte membrane, denoted as ALLTO.

[0080] Depend on Figure 4 (a) and (b) show that the thickness of the prepared ALLTO is about 200 μm, and the LLTO nanofibers are arranged in parallel orientation at the microscopic level, while the PEO / LiTFSI composite is uniformly filled therein.

[0081] Comparative Example 2

[0082] This comparative example provides a composite solid electrolyte and a preparation method thereof, which is different from comparative example 1 in that the type of inorganic skeleton material is different. The spinning solution in (1) of comparative example 1 is replaced with LLZAO electrospinning solution (specific chemical formula is Li 6.4 La3Zr2Al 0.2 O 12 ). First, add 23g of DMF and 2g of acetic acid solution into the bottle, then add lithium nitrate (0.531g, 15wt% excess), lanthanum nitrate hexahydrate (1.299g), zirconium n-propoxide (70wt% dispersed in 1-propanol, 0.936g), and aluminum nitrate nonahydrate (0.075g) into the bottle according to a fixed stoichiometric ratio, and stir the prepared solution for two hours. After the salt is completely dissolved, add the pre-prepared PVP powder (2.25g). Finally, stir the mixed solution overnight to complete the preparation of the electrospinning solution. The remaining steps are the same as those in Comparative Example 1. The prepared composite solid electrolyte membrane is recorded as ALLTO-2.

[0083] Comparative Example 3

[0084] This comparative example provides a composite solid electrolyte and a preparation method thereof, which differs from comparative example 1 in that the type of toughening material is different. The polymer in (3) of comparative example 1 is replaced by PVDF-HFP (weight average molecular weight of 400000 g / mol), and the solvent required for dissolution is replaced by DMF. The remaining steps are the same as those of comparative example 1. The prepared composite solid electrolyte membrane is recorded as ALLTO-3.

[0085] Comparative Example 4

[0086] This comparative example provides a composite solid electrolyte and a preparation method thereof, which differs from comparative example 1 in that the type of lithium salt is different. LiTFSI in (4) of comparative example 1 is replaced by lithium bis(fluorosulfonyl)imide (LiFSI), and the remaining steps are the same as comparative example 1. The prepared composite solid electrolyte membrane is denoted as ALLTO-4.

[0087] Comparative Example 5

[0088] This comparative example provides a composite solid electrolyte and a preparation method thereof, which is different from comparative example 1 in that the thickness of the electrolyte membrane is different. The thickness of the electrolyte membrane in (4) of comparative example 1 is changed to 100 μm, and the remaining steps are the same as comparative example 1. The prepared composite solid electrolyte membrane is recorded as ALLTO-5.

[0089] Test Example 1

[0090] The ionic conductivity of the composite solid electrolyte membranes obtained in Examples 1 to 5 and Comparative Examples 1 to 5 at different temperatures was tested by electrochemical impedance spectroscopy. Some of the test results are shown in FIG. Figure 5 As shown in (a), it can be seen that the ionic conductivity of VLLTO is significantly higher than that of ALLTO in the entire test temperature range. The test results of all samples at 60°C are shown in Table 1. It can be seen that the ionic conductivity of the composite solid electrolyte membranes obtained in all embodiments is higher than that of the corresponding comparative examples.

[0091] Table 1 Ionic conductivity test results of various embodiments and comparative examples at 60°C

[0092]

[0093]

[0094] Test Example 2

[0095] The composite solid electrolytes obtained in Examples 1 to 5 and Comparative Examples 1 to 5 are used to assemble Li-LFP full batteries. The specific assembly sequence of the solid-state battery is as follows: assemble from the positive electrode shell, assemble in the order of positive electrode shell, positive electrode sheet, composite solid electrolyte, lithium sheet, gasket, spring sheet and negative electrode shell, and then use a tablet press for packaging. The entire step is carried out in a glove box.

[0096] The assembled Li-LFP full battery was subjected to rate performance test and cycle performance test at different current densities by constant current charge and discharge. Figure 5 As can be seen in (b), the rate performance of VLLTO is significantly better than that of ALLTO, and it can still provide a discharge capacity of 133.1 mAh / g at a high rate of 2C. Figure 5 As can be seen in (c), the cycle performance of VLLTO is significantly better than that of ALLTO, and the discharge specific capacity is 116.9 mAh / g after 200 charge and discharge cycles, and the capacity retention rate is as high as 77.42%.

[0097] Test Example 3

[0098] The composite solid electrolytes obtained in Examples 1 to 5 and Comparative Examples 1 to 5 are used to assemble Li-Li symmetric batteries. The specific assembly order of the solid-state battery is as follows: assembling starts from the positive electrode shell, and assembles in the order of the positive electrode shell, lithium sheet, composite solid electrolyte, lithium sheet, gasket, spring sheet and negative electrode shell, and then uses a tablet press for packaging. The entire step is carried out in a glove box.

[0099] The assembled Li-Li symmetric battery was charged and discharged at a constant current of 0.1 mA / cm 2 The cycle performance test was carried out at a current density of Figure 5 It can be seen from (d) that during the entire cycle, the overpotential of VLLTO is significantly lower than that of ALLTO, while ALLTO not only has a higher overpotential, but also occasionally shows unstable fluctuations in the voltage-time curve.

[0100] Finally, it should be noted that the above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Obviously, for those skilled in the art, various changes and modifications can be made to the present invention without departing from the spirit and scope of the present invention, and the present invention is intended to include these changes and modifications.

Claims

1. A vertically oriented ceramic fiber / polymer composite solid electrolyte membrane, characterized in that: The composite solid electrolyte membrane is composed of an inorganic skeleton material with a vertically oriented structure and a toughening matrix material filled in the inorganic skeleton material. The inorganic skeleton material is an inorganic ceramic nanofiber with high lithium ion conductivity, and the toughening matrix material is a polymer / lithium salt composite with relatively high lithium ion conductivity.

2. The vertically oriented ceramic fiber / polymer composite solid electrolyte membrane according to claim 1, characterized in that: The inorganic skeleton material is an inorganic ceramic nanofiber with a continuous fast ion transmission path prepared by electrostatic spinning and subsequent high-temperature calcination process.

3. The vertically oriented ceramic fiber / polymer composite solid electrolyte membrane according to claim 2, characterized in that: The inorganic ceramic nanofibers are at least one or more of perovskite-type ceramic lithium lanthanum titanate, garnet-type ceramic lithium lanthanum zirconium oxide, sodium superion conductor-type ceramic lithium germanium aluminum phosphate, lithium titanium aluminum phosphate and all corresponding heteroelement-doped modified variant ceramics.

4. The vertically oriented ceramic fiber / polymer composite solid electrolyte membrane according to claim 1, characterized in that: In the inorganic skeleton material structure, the inorganic ceramic nanofibers present a highly ordered orientation structure and are oriented at any angle to the plane of the entire composite solid electrolyte membrane.

5. The vertically oriented ceramic fiber / polymer composite solid electrolyte membrane according to claim 4, characterized in that: In the inorganic skeleton material structure, the inorganic ceramic nanofibers present a highly ordered orientation structure and are arranged vertically at an angle of 90° with the plane of the entire composite solid electrolyte membrane.

6. The vertically oriented ceramic fiber / polymer composite solid electrolyte membrane according to claim 1, characterized in that: The polymer in the toughening matrix material is at least one or more of polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, and polymethyl methacrylate.

7. The vertically oriented ceramic fiber / polymer composite solid electrolyte membrane according to claim 1, characterized in that: The lithium salt in the toughening matrix material is at least one or more of lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(oxalatoborate), and lithium difluorooxalatoborate.

8. The vertically oriented ceramic fiber / polymer composite solid electrolyte membrane according to claim 1, characterized in that: The mass ratio of the inorganic skeleton material to the toughening matrix material is 10-60%:40-90%, and the sum of the mass ratios is 100%; and the mass ratio of the polymer and the lithium salt in the toughening matrix material is 80-90%:10-20%, and the sum of the mass ratios is 100%.

9. The vertically oriented ceramic fiber / polymer composite solid electrolyte membrane according to claim 1, characterized in that: The composite solid electrolyte membrane has a thickness of 50 to 300 μm.

10. A method for preparing the vertically oriented ceramic fiber / polymer composite solid electrolyte membrane according to any one of claims 1 to 9, characterized in that: The inorganic ceramic nanofibers and the spinning aid polyvinyl pyrrolidone are fully mixed and dissolved in an organic solvent to form a spinning solution, and an oriented inorganic ceramic nanofiber precursor film is obtained by electrostatic spinning and collected by a high-speed receiving roller. A vertically oriented inorganic ceramic nanofiber precursor array cylinder is then formed by winding, and then a vertically oriented inorganic ceramic nanofiber array cylinder is obtained by a calcination process. A solution containing a toughening matrix material is continuously poured into the cylinder to remove the organic solvent component therein, and finally the vertically oriented inorganic ceramic nanofiber / polymer composite solid electrolyte membrane is obtained by cutting with a thinning slicer.

11. The preparation method according to claim 10, characterized in that: The organic solvent in the spinning solution is N,N-dimethylformamide, the weight average molecular weight of the spinning aid polyvinyl pyrrolidone is 1300000 g / mol, the concentration is 6-14 wt%, and the concentration of various salts containing metal elements required for inorganic ceramic nanofibers is 15-25 wt%.

12. The preparation method according to claim 10, characterized in that: The conditions of the electrospinning include: The positive voltage is 10~20kV, the negative voltage is -2~0kV, The spinning temperature is 20-40°C, the spinning humidity is controlled at 20-50% RH, and the spinning time is 2-8 hours. The spinning needle injection speed is 0.4-1mL / h, and the receiving distance is 10-20cm. The high-speed receiving roller has a diameter of 5 to 15 cm and a rotation speed of 2000 to 4000 rpm.

13. The preparation method according to claim 10, characterized in that: In the calcination process, a staged heating method is adopted to achieve the removal of the spinning aid polyvinyl pyrrolidone and the formation of the inorganic ceramic nanofibers; the heating program is: The temperature was raised from room temperature to 100°C for 40 minutes. The temperature rises from 100°C to 600°C, and the heating time is 370 minutes. The temperature rises from 600℃ to 800℃, and the heating time is 70min. Keep at 800℃ for 600min and finally cool naturally to room temperature.

14. The preparation method according to claim 10, characterized in that: In the solution containing the toughening matrix material, the concentration of the toughening matrix material is 5-10wt%, and the selected organic solvent is one or more of acetonitrile, N,N-dimethylformamide (DMF), chloroform and the like.

15. The preparation method according to claim 10, characterized in that: The thinning and slicing is carried out in a low temperature environment of -20 to 10°C. The slicing is carried out in a direction perpendicular to the oriented arrangement direction of the inorganic ceramic nanofibers. The slice thickness is set by a slicer and controlled within a range of 50 to 300 μm.

16. A solid-state lithium metal battery, characterized in that It comprises a positive electrode, a negative electrode and the vertically oriented ceramic fiber / polymer composite solid electrolyte membrane according to any one of claims 1 to 9.

Citation Information

Cited By

  • Composite solid electrolyte membrane, preparation method thereof and lithium metal battery

    CN120727944A

  • Solid electrolyte, preparation method thereof and solid-state battery

    CN121862818A

  • Polymer composite solid electrolyte, battery and preparation method thereof

    CN121885749A